Completeness of intervention description in invasive cardiology trials: an observational study of ClinicalTrials.gov registry and corresponding publications - Lišnić, Viktoria; Ashraf, Hishaam; Viđak, Marin; Marušić, Ana (Frontiers in Medicine, 2023)
Introduction: Non-pharmacological invasive interventions in cardiology are complex and often inadequately reported. Template for Intervention Description and Replication (TIDieR) checklist and guide were developed to aid reporting and assessment of non-pharmacological interventions. The aim of our study was to assess the completeness of describing invasive cardiology interventions in clinical trials at the level of trial registration and corresponding journal article publication. Methodology: We searched for clinical trials in invasive cardiology registered in Clinicaltrials.gov and corresponding journal publications. We used the 10-item TIDieR checklist for registries and 12-item checklist for journal publications. Results: Out of 7,017 registry items retrieved by our search, 301 items were included in the analysis. The search for corresponding published articles yielded 192 journal publications. The majority of trials were funded by the industry and were medical device trials. The median number of reported TIDieR items was 4.5 (95% CI 4.49-4.51) out of 10, and while the corresponding journal articles reported 6.5 (95% CI 6.0-6.5) out of 12 TIDieR items.